Konsep Nafkah Istri Ketika Harga Kebutuhan Daruri Mahal Dalam Perspektif Hukum Islam - Risna Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to understand the concept of a wife's income from an Islamic legal perspective. And to find out whether the husband is obliged to increase his wife's income when the price of household necessities is expensive from an Islamic legal perspective. This research was conducted using library research and paying attention to the field (Field). Research). Literature study is a process of searching for various literature, the results of studies related to the research to be carried out. Literature study can be likened to a key that will open everything that can help solve research problems. The research results show that a wife's maintenance from the perspective of Islamic law is obligatory for husbands who have reached puberty in a virtuous way, namely in a way that is appropriate to their circumstances and abilities, whether they are well off (rich) or not (poor). This maintenance is obligatory on condition that (1) the wife surrenders herself to her husband completely, (2) the wife is an adult and capable of carrying out husband and wife relations, (3) the marriage that takes place includes a valid marriage contract, (4) the husband is not lost in the event of detention The wife is by his side without syar'i permission. The husband is obliged to increase the wife's living when the price of Daruri's needs is expensive from the perspective of Islamic law for a husband who is rich or capable. If the husband is poor, the wife has the right to receive a living just to meet her needs, food and side dishes that are good, and clothes just to meet her needs. If the husband belongs to the mutawasith (middle) group, his income should be looser, and his clothes should also be better. And Daruri's livelihood is (1) living accommodation, even though he is only able to rent a house. The most important thing is that the children and wife do not get hot, don't get caught in the rain, and are protected from the threat of criminals and wild animals. Relating to the wife's right to receive a place to live or the husband's obligation to provide a place to live. And (2) kiswah living means living in the form of clothing or clothing, which includes the costs of physical care for the wife, health care costs, jewelry costs, recreation costs, children's education costs, and other unexpected costs.